Mary Grace McNamara. The Disadvantage of Virtual Special Education - McNamara, Mary Grace (Young Scholars Grinchenko – Seton International Journal, 2021)
On March 15, 2020 the state of New Jersey was put into a lockdown due to the Coronavirus pandemic. As a result, schools were shut down, transitioning instruction from traditionally in-person to online. Since March, schools in New Jersey have not been entirely in person at full capacity, thus affecting the education of students K-12. Specifically, this article will cover observed trends in special education for middle school students.